Avaliação das normas voltadas ao licenciamento ambiental nos estados de Rondônia, Amazonas e Pará no que tange à garantia do desenvolvimento sustentável - Lopes, Emile da Cruz (Brasil, 2022)
Environmental licensing is one of the instruments for the implementation of the National Environment Policy (PNMA)and f erramenta legal aimed at protecting the environment. It has an important role in legal support to environmental agencies so that they can control and monitor economic activities that cause significant environmental impact on the environment, and there is a needfor standards to reconcile economic development according to the preservation of the environment and ensure that the activities occur in an ecologically sustainable manner. This study aims to conduct a literature review on the theme "Thevalue of environmental licensing standards in the states of Rondônia, Mazonas and Pará with regard to the guarantee of sustainable development". As a methodological procedure, a bibliographical research was carried out, through the evaluation of licensing standards, in the three states of the northern region of Brazil, in order to elaborate a diagnosis of positive and negative points in this evaluation. Based on comparative analysis, the three states presented legal order with the capacity to effectively ensure ecologically sustainable development, both have a wide variety of modalities of environmental authorisations or permits. However, with specific criteria, it was possible to verify that the state of Rondônia has the most appropriate normative basis to the current times, giving it greater capacity to ensure ecologically sustainable economic development for this region, thus demonstrating to be softer in relation to the frequency at which the entrepreneur must request the renewal of licenses.